Mercadotecnia de ciudades con fines turísticos: como se vender una ciudad? - Meléndez Urdaneta, Anaida; Rojas, Luis Rodolfo (Revista Turismo em Análise, 2000)
This article based on references from Europe and United States experiences, where came out the importance of the cities in social and economical development. It also considers that Venezuela needs application of new policies and strategies to the urban development and the local authorities involvement in order to have a better life quality. The general proposition consists in marketing tecniques applications on the existent resources and urban services, to obtain a competitive advantage. This will be used by the urban management to attend the local resident needs and to improve the cities attractiveness, which will generate positives impacts on tourist flow in urban areas. This article uses Venezuela as an example and describes the marketing techniques apllied to the cities.